Analisis Kegiatan Pembiayaan Akad Mudarabah di BMT Syariah Sejahtera Boyolali - Santoso, Harun (IAIN Salatiga, 2012)
This research was field research to investigate the implementation of mudarabah contract finance in BMT Syariah Sejahtera Boyolali in 2009. The research method was conducted using analysis descriptive method. The data obtained from the library and field studies would later be analyzed qualitatively, and would finally be described to obtain an objective illustration. The research result shows that the realization of mudarabah contract finance activity in BMT Syariah Sejahtera, principly propose to felling of believing to each other between the customer and BMT Syariah Sejahtera Boyolali side. That is reflected in the mudarabah contract. While the way of lawsuit solving is using the saving step first. This saving step consists of fourways, the are pressing ia claim instensively, reschedulling, reconditioning and restructuring. If those be finished so the last way that be taken is guarantee confiscatian